Media coverage and stock returns on the London Stock Exchange, 1825-70 - John D. Turner; Qing Ye; Clive B. Walker (Queen's University Centre for Economic History (QUCEH), 2016)
News media plays an important role in modern financial markets. In this paper, we analyse the role played by the news media in an historical financial market. Using The Times's coverage of companies listed on the London stock market between 1825 and 1870, we examine the determinants of media coverage in this era and whether there was a media discount. Our main finding is that a media discount only manifests itself after the mid-1840s and that the introduction of arm's-length ownership along with markedly increased market participation was the main reason for the emergence of this discount.
Keywords: G12; N23; 330; media; financial press; historical stock markets; advertising